1973
DOI: 10.2134/agronj1973.00021962006500050048xa
|View full text |Cite
|
Sign up to set email alerts
|

Thatch Accumulation in Bermudagrass Turf in Relation to Management1

Abstract: Thatch accumulation and decomposition in a ‘Tifgreen’ bermudagrass [Cynodon dactylon (L.) Pers.] putting green was studied in relation to fertility, fungicides, and clipping management. The effects of these practices were evaluated by measuring total thatch accumulation, lignin content of thatch, and soil microbial activity.Two sources of N, (NH4)2SO4 and activated sewage sludge (Milorganite), were applied at rates 0.25 and 0.75 kg/100 m2 every 2 weeks. Potassium was applied at two rates, 0 and 0.75 kg/100 m2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…There were no differences in thatch depth due to N source (sewage sludge or NH 4 NO 3 ). Conversely, other research suggested that slow‐release N sources sometimes reduced thatch, as compared to soluble N sources (Meinhold et al, 1973; Sartain, 1985). In our study N source had no effect on thatch depth.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…There were no differences in thatch depth due to N source (sewage sludge or NH 4 NO 3 ). Conversely, other research suggested that slow‐release N sources sometimes reduced thatch, as compared to soluble N sources (Meinhold et al, 1973; Sartain, 1985). In our study N source had no effect on thatch depth.…”
Section: Resultsmentioning
confidence: 90%
“…Of these cultural practices, only topeither had the highest shoot density or was in the top dressing significantly affected thatch ϩ mat depth, with group of cultivars with high shoot densities. In general, more thatch ϩ mat in the plots that were topdressed 4 over two years of sampling, shoot densities of the bertimes a year (White and Dickens, 1984). There were no mudagrasses followed the following trend: Champion differences in thatch depth due to N source (sewage and Mobile 9 with highest shoot densities; TifEagle, sludge or NH 4 NO 3 ).…”
Section: Bermudagrass and P Trivialis Shoot Densitiesmentioning
confidence: 92%
“…Extensive research is being carried out in the Mediterranean region and in California, the main goal of which is to decrease the amount of labor needed for olive harvesting. Efforts to decrease labor consumption are directed along two channels: via a mechanical solution (8, 13), a chemical solution (4,6,10,11) , and a combination of the two (2, 7,…”
Section: Increasing the Effectiveness Of Ethephon For Olive Harvestin...mentioning
confidence: 99%